Study on the cutter wear based on the cutterhead working status monitoring system in TBM tunneling - Gong, Qiuming; Xie, Xingfei; Wu, Fan; Liu, Junhao; Xing, Hai; Ren, Hongzhuan; Zhang, Hongwei; Xiao, Yuhang (Expanding Underground - Knowledge and Passion to Make a Positive Impact on the World, 2023)
TBM cutters are firmly in contact with the face when TBM is tunneling in the hard rock mass, and the cutter wear rate strongly affects TBM tunneling efficiency. However, the traditional manual measurement of the cutter wear has many limitations, such as the high labor intensity and potential measurement errors, while the most critical one is the manual measurement could not monitor the cutter wear in real-time. Consequently, the excessive and abnormal cutter wear cannot be timely found, which may cause some construction accidents. To tackle this problem, a cutterhead working status monitoring system was applied in several tunnel sites to monitor the cutter wear in real-time. Based on the collected data, three different cutter wear indexes were compared, and the most appropriate one was the loss millimeters in cutter radius per excavated rock mass volume, wv(mm/m3). The normal cutter wear process curve was analyzed with the cutter tip shape and was divided into three stages, which were the acceleration wear stage, deceleration wear stage, and uniform wear stage, respectively. Finally, a simple equation was set up to predict the cutter wear based on the obtained datasets.